Preliminary evaluation of technetium-99m-labeled thymoquinone - Elaridi, Jomana (2017)
Thymoquinone (TQ) was radiolabeled with sodium pertechnetate (Na 99m TcO4) by reduction with stannous chloride (SnCl2). The labeling efficiency of 99m Tc-TQ was determined by iTLC. Labeling conditions were optimized for pH, amount of SnCl2 required for radiolabeling and incubation time. Specifically, direct radiolabeling of 2.5 mg/ml TQ with 250 µg/ml of stannous chloride at pH 7 with gentle mixing and incubation for 30 minutes generated the desired 99m Tc-TQ complex with 95% labeling efficiency. The in vitro stability in serum and physiologic saline showed that the radiolabeled complex was stable for 24 h. Based on the percent injected dose (%ID), the highest uptake of the 99m Tc-TQ was found in the RES post IV injection in normal mice. Oral administration of TQ led to predominant uptake of the radiolabeled complex in the stomach and the intestine. Thus, a quick, efficient and reproducible method for radiolabeling thymoquinone with the 99m Tc-radionuclide was developed and optimized. The TQ-radiotracer was evaluated for radiochemical purity, stability and tissue and organ distribution in mice.